OPTIMALISASI KINERJA MELALUI DISIPLIN KERJA, MOTIVASI, PELATIHAN DAN KOMPETENSI - Manafe, David (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study was conducted to measure performance optimization through dependent variables consisting of work discipline, motivation, training, and competence. The tests carried out include direct effect tests and indirect or mediation effect tests. The data analyzed were obtained from questionnaires distributed to 44 respondents who are employees of the Department of Population and Civil Registration of Kupang Regency, using a Likert scale of 1-5. This study employed a quantitative research method by developing six hypotheses. Further tests were conducted using SEM-PLS with the SmartPLS 4 analytical tool. The hypothesis testing results indicate that: (1) performance improvement is influenced by work discipline and motivation; (2) training can enhance performance through the mediating role of work discipline and motivation; (3) training affects work discipline and motivation; (4) competence only affects the motivation variable and does not influence the work discipline variable; (5) competence and training variables individually do not have an impact on performance; (6) work discipline and motivation also do not serve as mediators for the effect of competence on performance improvement. The findings of this study imply the necessity for organizations to effectively implement variables that can improve employee performance (discipline, motivation, and training) in a collaborative manner.